1992
DOI: 10.1108/eb045132
|View full text |Cite
|
Sign up to set email alerts
|

Automated library system migration in the United States

Abstract: The application of computer technology to routine procedures in libraries has been evolving for more than twenty years. As technology has made new applications possible and as library and vendor expertise has developed, some libraries today are working with a second or even a third system vendor. This paper reports on a survey of libraries in the United States which have changed vendors and it identifies commonality and variation in factors associated with automation system change by these libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Migration is a recurring event and äs many libraries find their present system unsatisfactory, they are facing system migration for the first, second or even third time. Pourciau (1992), in bis survey of 154 libraries, found that 87 had migrated. Obsolete hardware, lack of functionality, unresolved system problems, long response times, lack of confidence in current vendor, abandonment of system by vendor and user complaints were found to be the most prominent reasons for migrating.…”
Section: Introductionmentioning
confidence: 96%
“…Migration is a recurring event and äs many libraries find their present system unsatisfactory, they are facing system migration for the first, second or even third time. Pourciau (1992), in bis survey of 154 libraries, found that 87 had migrated. Obsolete hardware, lack of functionality, unresolved system problems, long response times, lack of confidence in current vendor, abandonment of system by vendor and user complaints were found to be the most prominent reasons for migrating.…”
Section: Introductionmentioning
confidence: 96%
“…Lester J. Pourciau (1992) has listed 23 factors which have been responsible for migration in various libraries. Of them he has listed the following 10 to be major and substantive: (1) unresolved system problems, (2) unacceptably long system response times, (3) obsolete hardware, (4) lack of confidence in the current vendor's future performance, (5) abandonment of system by vendor, ( 6) a new emphasis upon networking, ( 7) an altered commitment by a parent institution to its library, (8) dysfunctionality of the library system in relation to the institution's system, (9) attractiveness of new products offered by other vendors, and (10) user complaints about system performance.…”
Section: Introductionmentioning
confidence: 99%